FDG-PET Versus PSMA-PET: A Patient With Prostate Cancer. (July 2020) - Kichloo, Asim; Amir, Rawan; Aljadah, Michael; Wani, Farah; Solanki, Shantanu; Singh, Jagmeet; Chugh, Savneek Singh
A 64-year old male presented to the hospital with a 1-week history of stools with bright red blood. Subsequent colonoscopy with a biopsy revealed a low-lying, moderately differentiated, rectal adenocarcinoma. A pelvic magnetic resonance imaging done afterwards showed a possible T3N1 rectal cancer with intact muscularis mucosa and a singular presacral lymph node enlargement. Furthermore, a suspicious peripheral prostatic enlargement and a possible left iliac crest sclerotic bone lesion were incidentally identified. 18 F-FDG (fluorodeoxyglucose) PET (positron emission tomography) scan confirmed a primary FDG avid rectal tumor and a presacral lymph node; however, there was no prostate or iliac crest uptake. A serum prostate-specific antigen performed in the hospital returned with a value of 37 ng/mL, which prompted a prostate biopsy, eventually returning as positive for adenocarcinoma. Consequently, a 68 Ga-PSMA PET scan to rule out possible metastatic prostate disease revealed increased PSMA expression in the prostate only. After consultation with the radiologist and nuclear medicine physician who concluded the iliac crest lesion is likely not cancerous, the final diagnosis of T3N1 rectal cancer with simultaneous high-grade prostate adenocarcinoma was declared. This case highlights the low sensitivity of 18 F-FDG PET scans for prostate cancer, the need for routine serum prostate-specific antigen screening, and the progression of 68 Ga-PSMA PET as a diagnostic tool for prostate cancer.